Ecological traits as predictors of avian reporting rates and monitoring gaps: a 12-year analysis of iNaturalist in Nigeria - Ringim, Abubakar Surajo; Muhammad, Sulaiman Inuwa; Abubakar, Haruna Mohammed (Frontiers in Bird Science, 2026)
To prioritise interventions amid the biodiversity crisis, this study applied a vulnerability framework to Nigerian avifauna by analysing 12 years of crowdsourced iNaturalist data (2013–2025). We defined vulnerability as a function of species’ sensitivity (extinction risk and specialization) and adaptive capacity (dietary breadth and movement). Analysing 8,751 research-grade records across 631 species, we tested how ecological traits predict IUCN status and reporting rates. Results showed a significant inverse association between adaptability and extinction risk. We identified a specialist penalty and monitoring gap: highly sensitive species contributed only 5% of the dataset, while generalists with high adaptive capacity dominated observations. Despite this bias, the data documented six new country records, including the African Rail (Rallus caerulescens) and Ross's Turaco (Musophaga rossae), as well as several range extensions. We conclude that while citizen science is a vital tool for monitoring common species and rapid discovery, targeted expert-led surveys remain essential for specialists. This study demonstrates that unstructured iNaturalist data can effectively inform the design of integrated biodiversity monitoring frameworks in West Africa.